Interior turbulence and the thresholding of atmospheres - Cottrell, Chris (Interstices: Journal of Architecture and Related Arts, 2014)
Turbulence, understood as a disruptive process of coming together, offers a productive metaphor for making sense of the complex dynamics involved in the formation and design of atmospheres. This paper extends the idea of turbulence to spatial, material, experiential and disciplinary registers, and examines the varied and sometimes contradictory forces that exist between them, with reference to an architectural installation project, Cloud Sound. An understanding of atmospheres as always in negotiation across a region of turbulence, rather than a static well-defined boundary, is developed. Cloud Sound sustains this uncertainty by keeping things unfixed and in play, part of an active process that I call thresholding. This concept is supported by a discussion of the ambiguity of atmospheres and how they disrupt distinctions between organisms and their environments, something that has implications for expanded disciplinary practises.